Use of nivolumab for colon cancer with Lynch syndrome - G. A. Khakimov (IP Habib O.N., 2020)
Lynch syndrome (LS), which occurs as a result of the defects in DNA mismatch repair, is characterized by an increased risk of colon, endometrial and urinary tract cancers. It is known that in case of colorectal cancer, the presence of high-frequency microsatellite instability (MSI-H) is associated with better survival rates, independent of other prognostic factors, including the stage of tumor development. Thus, in stage II sporadic colorectal cancer, MSI-H occurs in 22% of cases, in stage III in 12% of cases, and in stage IV only in 2% of cases. Regardless of the type of the tumor, immunotherapy using checkpoint inhibitors has been approved for treating patients with unresectable or metastatic tumors with deficient DNA mismatch repair (dMMR), this fact can be used as an approach to treatment patients with LS. The article describes the clinical observation of the patient with germline mutation in MLH1 gene, suffering from multiple primary malignancies of the colon, who has been receiving nivolumab for 26 months. This observation demonstrates the success of immunotherapy after sixth-line chemotherapy, showing the potential control of tumor growth in patients with LS.